P840 The HPV screening and vaccine evaluation (HPV-SAVE) study in men living with HIV: early pathologic and acceptability outcomes. (14th July 2019) - Grennan, Troy; Macpherson, Paul; Burchell, Ann; Claudio, Marian; Edward, Joshua; Gillis, Jennifer; Grace, Daniel; Nath, Ronita; Rosenes, Ron; Tan, Darrell; Salit, Irving
Abstract : Background: Anal cancer caused by oncogenic, high-risk (HR) human papillomavirus (HPV) is emerging as a leading cause of non-HIV-related death in HIV-positive MSM. Anal cancer rates in HIV-positive MSM are up to 100-times higher than the general population. There are no universally-accepted guidelines for anal cancer screening, even in high risk populations, due to a paucity of evidence to support its effectiveness. We assessed the acceptance rate to invitations for anal cancer screening, and describe preliminary pathology results. Methods: The HPV-SAVE Study is an ongoing Canadian study on screening and treatment of anal cancers and pre-cancers in HIV-positive MSM. Participants were invited to have anal cytology and HPV testing in their physician's office. Those with abnormalities were referred for high resolution anoscopy (HRA) and anal biopsies. Cytology was graded as per the Bethesda classification, and histology was described per the Lower Anogenital Squamous Terminology (LAST) nomenclature. Results: Out of 2241 invitations as of 01/2019, 617 men (27.5%) agreed to be screened. Cytology results from 518 satisfactory Pap tests were: 246 negative (47.5%), 62 LSIL (12.0%), 9 LSIL-H (1.7%), 14 HSIL (2.7%), 174 ASCUS (33.6%), and 13 ASC-H (2.5%). In 116 participants referred for HRA, 247 biopsies were done, yielding HSIL in 62 (53.4%) unique individuals, and one invasive carcinoma. In a sample of 127 participants, 111 (87.4%) had any HPV type, 82 (64.6%) had multiple HPV types, 78 (61.4%) had at least one high-risk HPV type, and 39 (30.7%) had HPV-16. Conclusion: MSM living with HIV had moderate acceptance of anal cancer screening invitations, with over half of screened men having abnormal cytology. A majority of those undergoing HRA had high-grade histology diagnosed, and most participants had HPV anal canal infection, with nearly two-thirds having anal canal infection with HR-HPV. These early results highlight the enormous HPV burden in this high-risk population. Disclosure: No significant relationships.